Dansk mediestøtte 1960-2014: Fra økonomisk kompensation til publicistisk motivation [Danish media subsidies 1960-2014: from economic compensation to publicist motivation] - Flensburg, Sofie (MedieKultur: Journal of media and communication research, 2015)
The article describes the historical development of Danish press subsidies from the 1960s until the passing of the 2013 Law on Media Subsidies. By mapping the changes in legislation, the political discussions and parliamentary processes it is shown that the media political discourse has changed over the last 50 years. State subsidies for the private press have gone from being a controversial political issue in the beginning of the period to becoming a legitimate tool for regulation of the media. This development suggests a growing resemblance between the Danish media policy and the traditions in the neighbouring Scandinavian countries, where direct press subsidies and a higher degree of state regulation have prevailed since the 1970s. In a media system perspective (Hallin and Mancini, 2004) the increasing legitimacy of press subsidies can be seen as a political ‘brake pad’ limiting the convergence with the liberal model and strengthening the corporate-democratic structures of the Danish media system.